The Language Functions Used in Guiding Conversation: Pragmatics Approach - I Gusti Ayu Agung Dian Susanthi; Made Sani Damayanthi Muliawan; Anak Agung Gede Suarjaya (RETORIKA: Jurnal Ilmu Bahasa, 2021)
The research about language in use is very important to be developed, it can be applied in every branches of studies for instance in tourism, economics, linguistics, etc. In communication people use language, so that in doing the interaction there are some expressions which have specific functions. This research aims to describe the formulation of language in use in guiding conversation and expressions can be used based on the formulation. The analysis of this research is language in use in guiding conversation. The data of this research were taken from the guiding conversation between guide and the guests during their travel in Ubud-Bali. The language function that can be used in Welcoming Guest at The Airport are expressive function consist of greeting and asking/getting information, informational function, and phatic function. Other than that, the language function used in Escorting the Guest to The Tourist Destination are expressive function, informational function, and directive function. Next, the language function used at Tourist Destination (Monkey Forest) are directive function, informational function, and directive function. The language used in Tourist Destination (Tegalalang Rice Terrace) are informational function, directive function consist of offering and suggestion. Language used in Tourist Destination (Tirta Empul) are informational function. While the language used in taking the Guest back to the Hotel are expressive and phatic function.